2006
DOI: 10.1787/377011785643
|View full text |Cite
|
Sign up to set email alerts
|

Globalisation and Inflation in the OECD Economies

Abstract: Over the past 25 years inflation has moderated considerably in all OECD economies. At the same time, the production of many goods and services has become increasingly internationalised and the level of trade between the OECD and non-OECD economies has risen markedly. This paper investigates the extent to which the observed changes in the inflation process can be attributed to the increasing integration of non-OECD economies into the global economy. The results of the analysis show that i) import prices have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Third, a number of empirical studies from very early on have challenged the notion that the flattening of the Phillips curve is much related to globalization-reporting mixed results on the relationship between openness and the sensitivity of inflation to the domestic (and even global) output gap over different time periods and across countries (see, e.g., IMF (2006IMF ( , 2013, Ball (2006), Pain et al (2006), Ihrig et al (2010), and Milani (2010). Figure I.B illustrates this same point suggesting that the inverse comovement between the import share and the slope of the Phillips curve on domestic slack implied by theory has leveled off or even reversed since 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Third, a number of empirical studies from very early on have challenged the notion that the flattening of the Phillips curve is much related to globalization-reporting mixed results on the relationship between openness and the sensitivity of inflation to the domestic (and even global) output gap over different time periods and across countries (see, e.g., IMF (2006IMF ( , 2013, Ball (2006), Pain et al (2006), Ihrig et al (2010), and Milani (2010). Figure I.B illustrates this same point suggesting that the inverse comovement between the import share and the slope of the Phillips curve on domestic slack implied by theory has leveled off or even reversed since 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, China imports signifi cant quantities of commodities such as iron, steel, non-ferrous metals and ores, and plastics. Accordingly, strong demand from China is often seen as a key driver of the rise in world commodity prices (see, for example, Pain et al, 2006;Bernanke, 2007;and Trichet, 2007). By contrast, India does not import many electronic and investment goods.…”
Section: China's and India's Roles In Global Tradementioning
confidence: 99%
“…Other studies convey similar messages, notwithstanding some differences: see, for example, Hawksworth (2006) or Poncet (2006). to recent increases in the prices of energy and other commodities, which may have been a source of upward pressure on infl ation over the past few years (see, for example, Pain et al, 2006;Bernanke, 2007;and Trichet, 2007). 2 Third, the rapid pace of China's and India's economic development is often related to mounting concerns about the risks of outsourcing manufacturing activities to China and services to India (see, for example, Head et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…3 Liberation (a daily French newspaper), November, 10th 2006, our translation. 4 A recent study published by the OECD (2006) has confirmed that globalization has only a small impact on consumer prices. Over the period 1995 to 2005, the net effect of imports from low-wage countries was small and consumer price inflation in Japan and the US "might have even been lower in the absence of globalization" (see OECD, 2006, p.38).…”
Section: Introductionmentioning
confidence: 99%